Effect of Groove Size on Mechanical Properties and Microstructure Due to Reinforcement Addition in Friction Stir Welded Dissimilar Alloys - Baridula, Ravinder Reddy; Ramaraju, Ramgopal Varma; C. K. M., Faizal; Abdullah, Ibrahim (Asian Research Publishing Network (ARPN), 2017)
Friction stir welding is a solid state joining technique, which improves the strength of the welded joint when compared to the fusion welding process. The strength of the welded joint can be further enhanced by the addition of reinforcements into the metal matrix during friction stir welding. In the present research, the dissimilar aluminium alloys AA5052 and AA6063 were welded by varying the groove size in order to estimate the strength of the joint due to reinforcements. The results show that varying the groove size influences the mechanical properties of the welded joint due to the variation of reinforcement’s deposition in the stir zone. The microstructure and elemental identification also show that the deposition of reinforcements was dependant on the groove size. Also, the width of the groove size plays a significant role on the strength of the welded joint, and maximum microhardness was found to be 150.08Hv for the groove size of 1 mm×2 mm.